Bone marrow breakout lesions act as key sites for tumor-immune cell diversification in multiple myeloma - Lutz, Raphael; Poos, Alexandra; Solé-Boldo, Llorenç; John, Lukas; Wagner, Johanna; Prokoph, Nina; Bärtsch, Marc-Andrea; Vonficht, Dominik; Palit, Subarna; Brobeil, Alexander; Mechtersheimer, Gunhild; Hildenbrand, Nina Marie; et al. (Science immunology, 2025)
The bone marrow microenvironment plays a crucial role in the development of multiple myeloma. As the disease progresses, malignant myeloma cells can evolve to survive outside the bone marrow. However, the processes underlying bone marrow independence and their consequences for immune control remain poorly understood. Here, we conducted single-cell and spatial multiomics analyses of bone marrow-confined intramedullary disease and paired breakout lesions that disrupt the cortical bone. These analyses revealed a distinct cellular microenvironment and architectural features of breakout lesions, characterized by extensive areas of malignant plasma cells interspersed with lesion-specific solitary natural killer and macrophage populations, as well as focal accumulations of immune cell agglomerates. Within these agglomerates, spatially confined T cell clones expanded alongside various immune cells, coinciding with the local genomic evolution of tumor cells. These analyses identify breakout lesions as a hotspot for tumor-immune cell interactions and diversification, representing a key event in myeloma pathogenesis.